Uncertainty quantification in the dynamics of a guyed mast subjected to wind load. (1st February 2017) - Ballaben, Jorge S.; Sampaio, Rubens; Rosales, Marta B.
Highlights: The stochastic dynamics of a guyed mast under wind load is studied. The wind load is found via the Spectral Representation Method. The randomness is due to the wind load and some structural parameters. The probability distributions are found with the Principle of Maximum Entropy. Guy pretension and nominal wind load are the most influential random parameters. Abstract: A study of the stochastic dynamics of a guyed mast under wind action is reported in the present work. The simplified structural model consists of a beam-column accounting for the second order effect due to axial loads and one inclined guy which is represented by a nonlinear extensible cable. The governing system is discretized with finite elements and a reduced order model is afterwards constructed using a basis of vibration modes. Both, the load and the structural model are considered stochastic. The wind load is derived from a wind velocity field after the application of the Spectral Representation Method. Since nonlinear structures show special sensitivity to dynamic loads, the reference nominal wind velocity (suggested by the codes) is also considered a random parameter. The guy pretension is a significant parameter in the behavior of guyed structures and its variation is a relevant issue. Furthermore, the bending stiffness can vary due to the structure reinforcements. Since it is not easy to foresee their behavior, an uncertainty quantification study appears necessary. After performing Monte Carlo simulations, the outcomes are evaluated accounting for each statistical parameter (guy tension, bending stiffness and wind nominal velocity) separately. Also, parameters combinations are studied. Six illustrative cases are reported. The results are shown in different ways (probability distribution functions (PDFs), correlation, exceeding limits, etc.). The stochastic variables have different effects on the statistics of the dynamic response. The guy pretension and the nominal wind velocity are found to be the most influential random quantities. Despite the potential of adverse impact, detailed studies of guyed structures under natural actions, as wind or earthquake, are not frequent. The involved variables are usually uncertain and it can be concluded that an uncertainty quantification study leads to a more realistic approach of the dynamic behavior of the structural system, in particular regarding the sensitivity to some parameters.